Analysis of the Paracoccidioides brasiliensis triosephosphate isomerase suggests the potential for adhesin function - Pereira, Luiz Augusto; Bao, Sonia Nair; Barbosa, Monica Santiago; da Silva, Juliana Leal M.; Felipe, Maria Sueli S.; de Santana, Jaime Martins; Mendes-Giannini, Maria José Soares [UNESP]; de Almeida Soares, Celia Maria (Blackwell Publishing, 2007)
Paracoccidioides brasiliensis is an important fungal pathogen. The disease it causes, paracoccidioidomycosis (PCM), ranges from localized pulmonary infection to systemic processes that endanger the life of the patient. Paracoccidioides brasiliensis adhesion to host tissues contributes to its virulence, but we know relatively little about molecules and the molecular mechanisms governing fungal adhesion to mammalian cells. Triosephosphate isomerase (TPI: EC 5.3.1.1) of P. brasiliensis (PbTPI) is a fungal antigen characterized by microsequencing of peptides. The protein, which is predominantly expressed in the yeast parasitic phase, localizes at the cell wall and in the cytoplasmic compartment. TPI and the respective polyclonal antibody produced against this protein inhibited the interaction of P. brasiliensis to in vitro cultured epithelial cells. TPI binds preferentially to laminin, as determined by peptide inhibition assays. Collectively, these results suggest that TPI is required for interactions between P. brasiliensis and extracellular matrix molecules such as laminin and that this interaction may play an important role in the fungal adherence and invasion of host cells.
Keywords: Paracoccidioides brasiliensis; TPI; interaction with epithelial cells; infection